(untitled) (Islas, 2026)
Introduction: Gender-based violence against Indigenous women constitutes a complex phenomenon intertwined with structural inequalities of gender, ethnicity, and class, whose understanding requires attention to the ways in which experience is discursively constructed. This study examines how Indigenous Andean women survivors of gender-based violence name and silence their experiences, with particular emphasis on the discursive resources through which they manage what can be said in restrictive sociocultural contexts. Methods: Using a qualitative approach rooted in Feminist Critical Discourse Analysis with a situated interpretive orientation, in-depth interviews with Indigenous women residing in different regions of Peru were analyzed. The analysis focused on identifying mitigation strategies, silences, narrative fragmentations, and subjective positioning, as well as the relationship between individual experiences and broader structural contexts. Results: The findings show that violence is neither named directly nor uniformly; rather, it is discursively constructed through linguistic resources that enable the negotiation of tensions between lived experience and the normative frameworks that regulate enunciation. Likewise, silences and hesitations emerge as meaningful discursive practices, revealing both the limits of language and the social conditions that constrain the expression of certain experiences. Agency appears as ambivalent and situated, challenging normative and linear conceptions of empowerment. Conclusions: This study contributes to the fields of discourse and gender studies by offering a contextualized reading of Indigenous women’s narratives of violence, highlighting the potential of Feminist Critical Discourse Analysis to examine experiences shaped by multiple inequalities.